PENERAPAN METODE LATIHAN (PENGUATAN) DENGAN PEMBERIAN KUIS DALAM PEMBELAJARAN SENI BUDAYA SISWA DI SMP NEGERI 2 PAINAN KABUPATEN PESISIR SELATAN - Wike Salvitri; Yos Sudarman; Tulus Handra Kadir (SENDRATASIK UNP, 2017)
AbstractThis article aims to finding out and describe the implementation of exersice method using quiz in cultural and art subject for student grade VIII at SMP N 2 Painan Kabupaten Pesisir Selatan. The design of the research was descriptive research by using qualitative approach. The object of the research were 4th grade student at SMP N 2 Painan. There were 20 students. The instrument was the researcher herself using stationary, camera and observation sheet. The research was conducted by observing the teacher while she is teaching and implementing the quiz. The data were collected through observation, interview, documentation and library research. The result of the research shows that the implementation of exercise method using quiz gave the positive effect to student in culture and art subject. It can be seen from student’s behavior that slowly improved since the first meeting the quiz given: such as they are serious during the lesson, gave response even asked some questions about what they learned. The learning outcomes also increase comparing to their midterm test result. It means the imolementation of quiz method is effective in cultural and art subject for student grade VIII 3 at SMP N 2 Painan.